Familial ureteroceles: an evidence for genetic background? - Sözübir, Selami; Ewalt, David; Strand, William; Baker, Linda A (The Turkish Journal of Pediatrics, 2005)
In the pediatric population, ureteroceles may present with different clinical pictures, and the severity of the renal damage is greater than in adults. Ureterocele, an anomaly of ureteric budding, is likely a component of a spectrum of anomalies including vesicoureteral reflux and ureteral duplications. Both have been confirmed to have a genetic and familial basis. We document the largest series of familial cases of ureteroceles, giving evidence for genetic background. We retrospectively reviewed the charts of patients with familial ureteroceles seen between 1992 and 2002. Coexisting ureteral anomalies and features of the cases were documented and compared to sporadic cases and all familial cases within the literature. This is the largest series of familial ureterocele patients in the literature. The review of the literature revealed seven publications with seven ureterocele families (15 affected patients) between 1936 and 2002. Comparing sex, ureterocele location, and single versus duplex systems, familial series are similar to other sporadic cases. Three of the families have twin siblings with ureteroceles. Familial cases, despite their rarity, raise the issue of the genetic origin of uretereoceles. Family members of ureterocele cases should be informed and followed carefully, especially twins. Increased reporting and genetic analysis of familial ureteroceles may prove to link the genetic mouse models of abnormal ureteric budding to the human conditions.